Characterization and application of biochar derived from greenhouse crop by-products for soil improvement and crop productivity in South Korea - Yu Na Lee; Sin Sil Kim; Dong Won Lee; Jae Hong Shim; Sang Ho Jeon; Ahn Sung Roh; Soon Ik Kwon; Dong-Cheol Seo; Seong Heon Kim (Applied Biological Chemistry)
Abstract The study examined the optimal production conditions and application rates of biochar derived from greenhouse crop by-products to enhance soil improvement and increase crop yield, thereby promoting sustainable agriculture in South Korea. The expansion of greenhouse cultivation has resulted in significant waste management challenges, and biochar production has emerged as a promising recycling solution for these by-products. Biochar was produced from red pepper stalks through pyrolysis at 200 to 600 °C, and its chemical properties, including pH, EC, T-C, and T-N, were analyzed. In this study, the chemical properties of biochar showed a significant increase in pH (from 5.8 to 10.3), EC (from 46.0 to 119.5 dS m⁻¹), and T-C (from 47.7 to 63.1%) with rising pyrolysis temperatures, while T-N decreased due to nitrogen volatilization above 300 °C. In the lettuce cultivation experiment, biochar application significantly improved fresh weight yield, with the biochar-treated group achieving a maximum of 83.3 g pot− 1 in the first cropping season, compared to 62.8 g pot− 1 in the NPK-only treatment group. However, excessive biochar application rates (≥ 800 kg ha⁻¹) led to yield reductions in the second cropping season, likely due to increased soil pH and EC. These results suggest the potential of recycling greenhouse crop residues into biochar to enhance soil fertility and crop productivity while indicating the need to manage application rates to minimize negative impacts from excessive use.